A Temperature‐Driven, Reversible, Helical‐Handedness Inversion in Peptaibol Analogues Tuned by the C‐Terminal Capping Moiety. (11th July 2019) - De Zotti, Marta; Syryamina, Victoria N.; Hussain, Rohanah; Longo, Edoardo; Siligardi, Giuliano; Dzuba, Sergei A.; Stella, Lorenzo; Formaggio, Fernando
Abstract: Trichogin is a natural peptide endowed with antimicrobial and antitumor activity. A member of the peptaibol family, trichogin possesses a C‐terminal amino alcohol. In the past, this moiety was substituted for a methyl ester for synthetic purposes and it was observed that this apparently slight modification caused significant changes in the peptide bioactivity. With the aim of understanding the reasons behind such observations, a detailed spectroscopic study on a number of trichogin analogues has been performed. Herein, data obtained from synchrotron radiation circular dichroism, NMR spectroscopy, and fluorescence spectroscopy in organic solvents at cryogenic temperatures are compared with those independently acquired by means of EPR spectroscopy at 80 K. It is unambiguously revealed that the presence of a reversible, temperature‐driven, screw‐sense interconversion from a right‐ to left‐handed helix is determined by the C‐terminal capping moiety. Data demonstrate, for the first time, the key role of a C‐terminal methyl ester in promoting peptide screw‐sense inversion. Abstract : With or without you : The propensity of a helical peptide to undergo thermodirected screw‐sense inversion is connected with its C‐terminal capping moiety. A C‐terminal methyl ester or carboxylic acid actively promotes the onset of a temperature‐driven screw‐sense inversion, whereas a C‐terminal amino alcohol hampers it.